Personality Traits and Charismatic Leader: An Innovative Perspective on Leadership - Giannoukou, Ioanna (Technium Business and Management, 2023)
This paper explores the relationship between inherent personality traits and the emergence of charismatic leadership qualities. Drawing from established psychological models, such as the Five Factor Model, we identify key personality traits most associated with charismatic leaders, including extraversion, openness to experience, and emotional intelligence. Using both historical analysis and contemporary case studies, we demonstrate how these traits often manifest in leaders recognized for their charisma. However, we also discuss the role of environmental factors and personal experiences in shaping and amplifying these traits. Furthermore, the potential pitfalls of over-relying on charisma, to the detriment of other leadership qualities, are highlighted. Overall, the research suggests that certain personality traits, such as extraversion and conscientiousness, are associated with charismatic leadership behavior. These traits contribute to the ability of leaders to influence and mobilize others, create a positive group dynamic, and promote environmental management initiatives. Understanding the relationship between personality traits and charismatic leadership can provide valuable insights for organizations in selecting and developing effective leaders. The paper concludes with recommendations for organizations on how to foster and recognize leadership potential by considering a balance of inherent traits, cultivated skills, and contextual understanding.